Isoliquiritigenin alleviates early brain injury after experimental intracerebral hemorrhage via suppressing ROS- and/or NF-κB-mediated NLRP3 inflammasome activation by promoting Nrf2 antioxidant pathway - Zeng, Jun; Chen, Yizhao; Ding, Rui; Feng, Liang; Fu, Zhenghao; Yang, Shuo; Deng, Xinqing; Xie, Zhichong; Zheng, Shizhong (Journal of neuroinflammation, 2017)
Intracerebral hemorrhage (ICH) induces potently oxidative stress responses and inflammatory processes. Isoliquiritigenin (ILG) is a flavonoid with a chalcone structure and can activate nuclear factor erythroid-2 related factor 2 (Nrf2)-mediated antioxidant system, negatively regulate nuclear factor-κB (NF-κB) and nod-like receptor family, pyrin domain-containing 3 (NLRP3) inflammasome pathways, but its role and potential molecular mechanisms in the pathology following ICH remain unclear. The present study aimed to explore the effects of ILG after ICH and underlying mechanisms. ICH model was induced by collagenase IV (0.2 U in 1 μl sterile normal saline) in male Sprague-Dawley rats weighing 280-320 g. Different doses of ILG (10, 20, or 40 mg/kg) was administrated intraperitoneally at 30 min, 12 h, 24 h, and 48 h after modeling, respectively. Rats were intracerebroventricularly administrated with control scramble small interfering RNA (siRNA) or Nrf2 siRNA at 24 h before ICH induction, and after 24 h, ICH model was established with or without ILG (20 mg/kg) treatment. All rats were dedicated at 24 or 72 h after ICH. Neurological deficits, histological damages, brain water content (BWC), blood-brain barrier (BBB) disruption, and neuronal degeneration were evaluated; quantitative real-time RT-PCR (qRT-PCR), immunohistochemistry/immunofluorescence, western blot, and enzyme-linked immunosorbent assay (ELISA) were carried out; catalase, superoxide dismutase activities and reactive oxygen species (ROS), and glutathione/oxidized glutathione contents were measured. ILG (20 and 40 mg/kg) markedly alleviated neurological deficits, histological damages, BBB disruption, brain edema, and neuronal degeneration, but there was no significant difference between two dosages. ILG (20 mg/kg) significantly suppressed the NF-κB and NLRP3 inflammasome pathways and activated Nrf2-mediated antioxidant system. Gene silencing of Nrf2 aggravated the neurological deficits, brain edema, and neuronal degeneration and increased the protein levels of NF-κB p65, NLRP3 inflammasome components, and IL-1β. ILG delivery significantly attenuated the effects of Nrf2 siRNA interference mentioned above. Intraperitoneal administration of ILG after ICH reduced early brain impairments and neurological deficits, and the mechanisms were involved in the regulation of ROS and/or NF-κB on the activation of NLRP3 inflammasome pathway by the triggering of Nrf2 activity and Nrf2-induced antioxidant system. In addition, our experimental results may make ILG a potential candidate for a novel therapeutical strategy for ICH.